Distribution of Anopheles gambiae thioester-containing protein 1 alleles along malaria transmission gradients in The Gambia - Majidah Hamid-Adiamoh; Abdoulie Mai Janko Jabang; Kevin Ochieng Opondo; Mamadou Ousmane Ndiath; Benoit Sessinou Assogba; Alfred Amambua-Ngwa (Malaria Journal, 2023)
Abstract Background Thioester-containing protein 1 (TEP1) is a highly polymorphic gene playing an important role in mosquito immunity to parasite development and associated with Anopheles gambiae vectorial competence. Allelic variations in TEP1 could render mosquito either susceptible or resistant to parasite infection. Despite reports of TEP1 genetic variations in An. gambiae, the correlation between TEP1 allelic variants and transmission patterns in malaria endemic settings remains unclear. Methods TEP1 allelic variants were characterized by PCR from archived genomic DNA of > 1000 An. gambiae mosquitoes collected at 3 time points between 2009 and 2019 from eastern Gambia, where malaria transmission remains moderately high, and western regions with low transmission. Results Eight common TEP1 allelic variants were identified at varying frequencies in An. gambiae from both transmission settings. These comprised the wild type TEP1, homozygous susceptible genotype, TEP1s; homozygous resistance genotypes: TEP1r A and TEP1r B , and the heterozygous resistance genotypes: TEP1sr A , TEP1sr B , TEP1r A r B and TEP1sr A r B . There was no significant disproportionate distribution of the TEP1 alleles by transmission setting and the temporal distribution of alleles was also consistent across the transmission settings. TEP1s was the most common in all vector species in both settings (allele frequencies: East = 21.4–68.4%. West = 23.5–67.2%). In Anopheles arabiensis, the frequency of wild type TEP1 and susceptible TEP1s was significantly higher in low transmission setting than in high transmission setting (TEP1: Z = − 4.831, P < 0.0001; TEP1s: Z = − 2.073, P = 0.038). Conclusions The distribution of TEP1 allele variants does not distinctly correlate with malaria endemicity pattern in The Gambia. Further studies are needed to understand the link between genetic variations in vector population and transmission pattern in the study settings. Future studies on the implication for targeting TEP1 gene for vector control strategy such as gene drive systems in this settings is also recommended.